Empirical Modeling of Material Removal Rate during the WEDM of Inconel 690 - Raj A.; Yadav L.K.; Misra J.P.; Upadhyay V. (My University, 2025)
Material Removal Rate (MRR) is considered as the most desirable process performance measure variable of WEDM process. Variability of MRR mainly depends on the selected input process variables of WEDM process. The goal of the current research is to improve MRR by optimizing the WEDM input processing parameters. In this experiment, an empirical model of MRR was created using the following four process input variables: Power-on time, power-off time, peak current (ip), and spark-gap voltage. Box-Behnken design (BBD) based on response surface methodology (RSM) was employed for individual responses and multiobjective/ responses optimization for high-performance WEDM attributes. The nuclear and gas turbine industry favors inconel 690 workpieces. To forecast the simplified state of input process variables, RSM-based mathematical modelling is applied. Additionally, ANOVA (Analysis of Variance) is employed to identify the relevant input process variables. The results show that peak current and power-on time are the most efficient variables for achieving high MRR. © 2023 Raj et al.